Therapeutic effect of thiocetam on the manifestations of ischemia-reperfusion complicated by massive blood loss and mechanical trauma - Volotovska, Nataliya (Journal of Education, Health and Sport, 2020)
Among the current medical and social problems, injuries and blood loss occupy a prominent place, causing stress on the antioxidant defenses. Hypoxia, which underlies the pathogenesis of the post-traumatic period of both diseases, leads to a significant imbalance in the work of internal organs. Scientists are increasingly attracted by the need to use a tourniquet or intraoperative ligatures, as reperfusion local and systemic damage develops. Antioxidants are considered a promising means of correction. The aim of the study was to investigate the features of metabolic disorders in the liver in the early post-traumatic period on the background of the use of a tourniquet and the effectiveness of thiocetam correction. Materials and methods. The experiment was perfomed on 130 white male rats (200-250 g), which were divided into 4 groups: control – the CG, the EG-1 – combination of limb ischemia-reperfusion (IR) with blood loss, the EG-2 – combination of limb IR with blood loss and mechanical trauma of the thigh; the EG-3 combination of limb IR, blood loss, mechanical injury and thiocetam administration. The Malonic dialdehide level catalase activity were estimated in the liver. Results. The use of thiocetam, which is able to struggle against of ischemia and lipid peroxidation by reactivating antiradical enzymes: superoxide dismutase, catalase and glutathione peroxidase, had a positive effect on the state of antioxidant and prooxidant units in the organ, located far from the place of primary ischemia-reperfusion. If in the group of untrated animals (the EG-2, where massive blood loss was combined with a thigh fracture and the use of hemostatic tourniquet) in the early period, the MDA level exceeded the CG data in 5,4 times, and on the 7th and 14th days remained high – being higher on 2,1 times and on 2,7 times, then in the EG-3 (group of treated animals) on the 1st day the level of MDA exceeded the CG data in 4,3 times, but on the 7th and 14th days was higher by 90,5 % and 64 % respectively. The supportive effect of thiocetam on the activity of catalase in the liver was also noted. Thus, in EG-2 the level of antioxidant enzyme on the 1st day decreased by 71,7 %, and remained almost at this level throughout the all post-experimental period. As for the group of treated animals, the level of activity on the 1st day after the intervention decreased by 44,7%, and was so for almost the entire period. On the 14th day, it remained reduced compared to the CG by 35,1 %, while in EG-2 this index was lower compared to the CG by 70,5 %. Conclusion. Having the positive effect of the introduction of thiocetam in the ischemic area, we can eventually add new complex, given the world experience, which would affect the development of the inflammatory response and the rheological properties of blood.